Exopolysaccharide Produced by Probiotic Strain Lactobacillus paraplantarum BGCG11 Reduces Inflammatory Hyperalgesia in Rats - Dinić, Miroslav; Pecikoza, Uroš; Djokić, Jelena; Stepanović-Petrović, Radica; Milenković, Marina; Stevanović, Magdalena; Filipović, Nenad; Begović, Jelena; Golić, Nataša; Lukić, Jovanka (Frontiers in Pharmacology, 2018)
The aim of this study was to test the potential of high molecular weight exopolysaccharide produced by the putative probiotic strain Lactobacillus paraplantarum BGCG11 (EPS CG11) to alleviate inflammatory pain in Wistar rats. The EPS CG11 was isolated from bacterial surface and was subjected to Fourier-transform infrared spectroscopy (FTIR) and thermal analysis. FTIR spectra confirmed the polysaccharide structure of isolated sample, while the thermal methods revealed good thermal properties of the polymer. The antihyperalgesic and antiedematous effects of the EPS CG11 were examined in the rat model of inflammation induced by carrageenan injection in hind paw. The results showed that the intraperitoneal administration of EPS CG11 produced a significant decrease in pain sensations (mechanical hyperalgesia) and a paw swelling in a dose-dependent manner as it was measured using Von Frey anesthesiometer and plethysmometer, respectively. These effects were followed by a decreased expression of IL-1β and iNOS mRNAs in rat’s paw tissue suggesting that the antihyperalgesic and antiedematous effects of the EPS CG11 are related to the suppression of inflammatory response. Additionally, we demonstrated that EPS CG11 exhibits immunosuppressive properties in the peritonitis model induced by carrageenan. Expression levels of pro-inflammatory mediators IL-1β, TNF-α and iNOS were decreased, together with the enhanced secretion of anti-inflammatory IL-10 and IL-6 cytokines, while neutrophil infiltration was not changed. To the best of our knowledge, this is the first study which reports an antihyperalgesic effect as the novel property of bacterial exopolysaccharides. Given the high demands of pharmaceutical industry for the replacement of commonly used analgesics due to numerous side effects, this study describes a promising natural compound for the future pharmacological testing in the area.